Laser-driven high-velocity microparticle launcher in atmosphere and under vacuum. (March 2020) - Veysset, David; Sun, Yuchen; Kooi, Steven E.; Lem, Jet; Nelson, Keith A.
Highlights: A laser-driven microparticle launcher with vacuum capabilities is described. Maximum velocities for particles of different types and masses are reported under atmospheric and low vacuum conditions. Velocities are limited by optical absorption saturation and particle strength and heat resistance. Under vacuum conditions, the blast wave generated upon laser ablation is largely suppressed and drag is reduced. The ballistic limit is measured for a polyethylene film and residual velocity is modeled using a Recht-Ipson model. Abstract: This paper presents a novel approach to launch single microparticles at high velocities under low vacuum conditions. In an all-optical table-top method, microparticles with sizes ranging from a few microns to tens of microns are accelerated to supersonic velocities depending on the particle mass. The acceleration is performed through a laser ablation process and the particles are monitored in free space using an ultra-high-speed multi-frame camera with nanosecond time resolution. Under low vacuum, we evaluate the current platform performance by measuring particle velocities for a range of particle types and sizes, and demonstrate blast wave suppression and drag reduction under vacuum. Showing an impact on polyethylene, we demonstrate the capability of the experimental setup to study materials behavior under high-velocity impact. The present method is relevant to space applications, particularly to rendezvous missions where velocities range from tens of m/s to a few km/s, as well as to a wide range of terrestrial applications including impact bonding and impact-induced erosion.